Cloning, Expression, and Functional Characterization of Secondary Amino Acid Transporters of Lactococcus lactis - Trip, Hein (American Society for Microbiology, 2013)
Fourteen genes encoding putative secondary amino acid transporters were identified in the genomes of Lactococcus lactis subsp. cremoris strains MG1363 and SK11 and L. lactis subsp. lactis strains IL1403 and KF147, 12 of which were common to all four strains. Amino acid uptake in L. lactis cells overexpressing the genes revealed transporters specific for histidine, lysine, arginine, agmatine, putrescine, aromatic amino acids, acidic amino acids, serine, and branched-chain amino acids. Substrate specificities were demonstrated by inhibition profiles determined in the presence of excesses of the other amino acids. Four knockout mutants, lacking the lysine transporter LysP, the histidine transporter HisP (formerly LysQ), the acidic amino acid transporter AcaP (YlcA), or the aromatic amino acid transporter FywP (YsjA), were constructed. The LysP, HisP, and FywP deletion mutants showed drastically decreased rates of uptake of the corresponding substrates at low concentrations. The same was observed for the AcaP mutant with aspartate but not with glutamate. In rich M17 medium, the deletion of none of the transporters affected growth. In contrast, the deletion of the HisP, AcaP, and FywP transporters did affect growth in a defined medium with free amino acids as the sole amino acid source. HisP was essential at low histidine concentrations, and AcaP was essential in the absence of glutamine. FywP appeared to play a role in retaining intracellularly synthesized aromatic amino acids when these were not added to the medium. Finally, HisP, AcaP, and FywP did not play a role in the excretion of accumulated histidine, glutamate, or phenylalanine, respectively, indicating the involvement of other transporters.